The health assessment needs of Kansas State students survey - Hernandez, Mayrena Isamar (Kansas State University, 2018)
INTRODUCTION: College represents a major stepping stone toward independence for a number of students. This transition from high school to college life is a critical period for development of a healthy lifestyle. Health promotion departments at universities are uniquely positioned to implement a comprehensive strategy for increasing physical activity, and advocate for healthful eating. The Kansas State University (KSU) Health Promotion team at Lafene Health Center helps students enhance their health behaviors, and they developed a questionnaire to better understand the health issues students face. Their questionnaire, The Health Assessment Needs of Kansas State Students (THANKS), was created to better understand the barriers to a healthful lifestyle for students at KSU. The purpose of the current study was to assess the THANKS (questionnaire)used in the Fall 2016 and Fall 2017 semesters within the student population at KSU. METHODS: The Fall 2016 and Fall 2017 THANKS questionnaires were analyzed for this investigation. The THANKS questionnaires focused on holistic aspects of health, including: physical activity, hydration, nutrition, tobacco use, mental health, social determinants of health, general health, and demographics. For the purpose of assessing this questionnaire, section A: Physical Activity (PA), section B: Nutrition, and section H: Demographics were analyzed. The following analyses were performed: readability analysis; the Flesch Reading Ease Score and Flesch Kincaid Grade Level score, descriptive statistics, reliability analysis; Cronbach’s Alpa and Cronbach’s Alpha if item deleted, and ANOVA. RESULTS: Overall, women made up the majority of the sample size (66.7%). Age ranges for ≤18 yrs old for all academic classifications were 72.3% (freshman) and 3.4% (sophomore). 19-24 yrs old age category had 93.3% (sophomore), 92.6% (Junior), 87.1% (Senior), whereas, graduate or professional students had 39.8% as their highest for the category of 25 to 30 yr olds. The majority of freshman resided in campus residence halls (75.3%), whereas for all classes respectively resided off campus (52.1%, 71.6%, 83.1%, 83%). The sample was primarily Caucasian for all classes (sophomore- graduate or professional), respectively (83.4%, 83.2%, 85.8%, 87.6%, 65.9%). Reliability analysis showed a low Cronbach’s Alpha for the PA section (0.58). For the nutrition section, frequency questions (0.61), and location of meals consumed had a high a high reliability (0.89). Flesch Reading Ease score of 70.3 indicated the THANKS survey is fairly easy to read. Flesch-Kincaid Grade Level score of 5.2 indicated the reader’s age of fifth graders. All inter-item correlations for the frequency of PA and location of engagement in PA were below 0.15, ANOVA of general nutritious diet and consumption of p-values of SSB (0.001), energy drinks (0.019), meals at home (0.007), meals off campus (0.000), meals at vending machine (0.031), glasses of water (0.001), participation in PA (0.000), frequency of moderate intensity (0.002), frequency of strength/resistance training (0.000) per week showed significance. ANOVA for participation in PA and of p-values SSB (0.001) per week and glasses of water per week (0.000) showed significance. CONCLUSION: The THANKS survey shows promise for an adequate survey tool but with room for improvement. Health promotion department may need to improve the psychometric properties of the PA and nutrition sections of the survey in order to obtain meaningful survey results that may be used in translation to programming for improved health on campuses.
Keywords: Health assessment; Questionnaire; College; Biostatistics; Public health